Kombinasi Teknik Effleurage Massage dan Terapi Akupresur terhadap Nyeri Punggung Ibu Hamil Trimester III: Combination of Effleurage Massage Techniques and Acupressure Therapy for Back Pain among Third Trimester Pregnant - Arini Purnama Sari; Farida Farida (Poltekkes Kemenkes Palu, 2021)
Introduction: One of the complaints that is often felt by pregnant women in the third trimester is back pain. Back pain occurs in the lumbar sacral area and usually the pain will increase with gestational age. There are several non-pharmacological therapies that are often used to minimize pain, namely effleurage massage techniques and acupressure therapy. Purpose: This study was to determine the effect of the combination of effleurage massage technique and acupressure therapy on back pain in third trimester pregnant women. Methods: Quasi-experimental research method, one group pretest and posttest design. Samples were taken by purposive sampling obtained 24 third trimester pregnant women with back pain. Data collection was carried out in May-August 2021. Data collection used a numerical pain intensity questionnaire VAS (Visual Analog Scale) intensity (0-10). The effleurage massage technique was carried out in a right tilted position, then continued with acupressure therapy by pressing the BL 23 meridian point 3 times a week. Data analysis using Wilcoxon test. Results: There was a decrease in the mean of back pain before that was 2.83 and after 1.46 with a mean difference of 1.37. Wilcoxon test results obtained sig value is <0.0001. Conclusion: The combination of effleurage massage technique and acupressure therapy is effective in reducing back pain in third trimester pregnant women.